Fruit extracts of various cornelian cherry (Cornus mas L.) cultivars as antioxidant therapy for alleviating nitrative stress in erythrocytes of blood in experimental diabetes mellitus - I. V. Brodyak; A. A. Moroz; A. Z. Kucharska; N. O. Sybirna (Zaporozhye State Medical University, 2024)
Natural antioxidants (vitamins, bioflavonoids, anthocyanins, etc.) are used to prevent the development of oxidative-nitrative stress in diabetes mellitus (DM), which helps to restore or avert functional disorders in the cells and tissues of the body. The aim of the study is to investigate the effect of extracts of the fruit of different cultivars of the cornelian cherry, as well as their main iridoid glycoside - loganic acid, on the activity of NO-synthase and the content of stable metabolites of NO in blood erythrocytes of rats with streptozotocin-induced diabetes. Materials and methods. In the work, we used the extract of the fruits of the cornelian cherry "Podolski" cultivar (BDPA 10462), the ripe fruits of which have a red color, and the extract of the "Yantarnyi" (BDPA 14131) and "Flava" (BDPA 8795) cultivars, the ripe fruits of which have a yellow color. Loganic acid was extracted from yellow fruits of the "Yantarnyi" and "Flava" cultivars of Cornus mas L. All studied extracts were administered to rats orally for 14 days from the 10th day after the induction of DM. The dose of administration was 20 mg/kg body weight. Results. The extract of the red fruits is demonstrated the most pronounced effect in normalizing the biomarkers of nitrative stress (activity of NO-synthase and its isoforms, the content of nitrite and nitrate anions) in erythrocytes of rats with diabetes. The extract of the yellow fruits shows a positive effect on the suppression of nitrative stress, which has been indicated by a decrease in the activity of iNO-synthase to the values in the control group of animals. Loganic acid, on the contrary, inhibited the eNO-synthase. In addition, the extract of yellow fruits of cornelian cherry and loganic acid decreased the level of NO3- and increased the content of NO2- in erythrocytes of diabetic rats. Conclusions. Biomarkers of nitrative stress in erythrocytes of rats with streptozotocin-induced diabetes indicated the antioxidant properties of fruit extracts of cornelian cherry, in particular the red fruits, which contain a large amount of anthocyanins.